Paediatric acute rheumatic fever in developed countries: Neglected or negligible disease? Results from an observational study in Lombardy (Italy) - Viorica Munteanu; Antonella Petaccia; Nicolae Contecaru; Emanuele Amodio; Carlo Virginio Agostoni (AIMS Press, 2018)
Introduction: Acute Rheumatic Fever (ARF) is a multisystemic disease that results from an autoimmune reaction due to group A streptococcal infection. The disease affects predominantly children aged 5 to 15 years and although its incidence in developed Countries declined since the early 1900s, to date there is a paucity of data that confirm this epidemiological trend. Objective: The study aimed to assess the burden of ARF in term of hospitalization and to describe the characteristics of acute rheumatic fever (ARF) in the paediatric population of Lombardy. Study design: The study was carried out by analyzing hospital discharge records of patients resident of Lombardy and aged 0-17 years old who, from 2014 to 2016, were hospitalized with the diagnosis of ARF. The following variables have been studied: age, sex, municipality of residence, date of diagnosis of each patient, hospital of admission, and presentation of the disease. Results: From 2014 to 2016, 215 patients were found to meet the inclusion criteria and diagnosed as affected from Acute Rheumatic Fever. The rate of hospitalization showed a slightly increasing trend from 3.42 in 2014 to about 5.0 in 2016. Moreover, ARF presented a typical seasonal trend with lower cases in the autumn and a peak of hospitalization in the spring. Conclusion: To date, ARF seems to be a rare but not negligible disease in southern central European countries, and in Lombardy we estimated an annual hospitalization rate of 4.24 cases per 100,000 children. The increasing trend found in our study suggests that the burden of the disease could be reduced by involving multidisciplinary health professionals who, in addition to the paediatrician of free choice, would promote evidence based medicine management of the disease during all its clinical phases.